Summer of '69 [compact disc, unabridged] - Hilderbrand, Elin (Hachette Audio, 2019)
Follow New York Times bestselling author Elin Hilderbrand back in time and join a Nantucket family as they experience the drama, intrigue, and upheaval of a 1960s summer. Welcome to the most tumultuous summer of the twentieth century! It's 1969, and for the Levin family, the times they are a-changing. Every year the children have looked forward to spending the summer at their grandmother's historic home in downtown Nantucket: but this year Blair, the oldest sister, is marooned in Boston, pregnant with twins and unable to travel. Middle sister Kirby, a nursing student, is caught up in the thrilling vortex of civil rights protests, a passion which takes her to Martha's Vineyard with her best friend, Mary Jo Kopechne.